Nanostructured ultrathin catalyst layer based on open-walled PtCo bimetallic nanotube arrays for proton exchange membrane fuel cells. (April 2017) - Zeng, Yachao; Shao, Zhigang; Zhang, Hongjie; Wang, Zhiqiang; Hong, Shaojing; Yu, Hongmei; Yi, Baolian
Abstract: Nanostructured ultrathin catalyst layer based on open-walled PtCo bimetallic nanotube arrays has been designed and constructed through a hydrothermal and physical vapor deposition method for proton exchange membrane fuel cells (PEMFCs). The open-walled PtCo bimetallic NTAs with a diameter ca. 100 nm were directly aligned with proton exchange membrane, forming an ultrathin catalyst layer with a thickness ca. 300 nm. The incorporation of Co in Pt is realized by a facile thermal annealing method, endowing the catalyst layer with improved activity. During the purification of catalyst-coated-membrane (CCM) electrode, the sealed off PtCo nanotubes cracked into open-walled nanotubes, making both the interior and exterior surfaces exposed to the surroundings. The catalyst layer is binder-free and beneficial for exposing catalytic active sites, enhancing mass transport during the operation of PEMFCs. Serving as cathode, a maximum power density of 14.38 kW gPt −1 was achieved with a cathodic Pt loading of 52.7 μg cm −2, which is 1.7 fold higher than the conventional CCM. Accelerated degradation test (ADT) manifests that the prepared nanostrucutred ultrathin catalyst layer is more stable than the conventional CCM. The proposed catalyst layer structure and also its preparation method hold great potential for PEMFCs and other applications. Graphical abstract: Nanostructured ultrathin catalyst layer based on open-walled PtCo bimetallic nanotube arrays has been designed and constructed for fuel cells. The concept is realized by hydrothermal synthesis and physical vapor deposition method. Beneficial from its structural advantages, a power density of 17.02 kW gPt −1 (anode) and 14.38 kW gPt −1 (cathode) has been achieved. And the advanced catalyst layer presented enhanced durability over the conventional catalyst layer. Highlights: A nanostructured ultrathin catalyst layer (NUCL) has been constructed for PEMFCs. The NUCL is based on open walled Co-doped Pt nanotube arrays (NTAs). The Co-doped Pt NTAs is prepared from a template-assisted deposition and etching strategy. Single cell test manifests that NUCL has a pronounced catalyst utilization and durability.